Binary goal programming approach to nurse scheduling problem in Davao medical Center. - Sebastian, Anna Jean L. (2007)
A 0-1 goal in programming model on nurse scheduling problem in Davao Medical Center was developed. The formulation of the model is based on the surveys and interviews conducted on particular respondents in DMC. The model minimizes the deviations from the corresponding goals subject to hospital policies and nurses? preferences. This model was applied to two sets of nurses: four regular nurse aids and four nurses (consisting of two contractual and regular nurses). The model generated schedule shows: lesser number of isolated days off, lesser number of assigned night shifts, and little difference in the distribution of shifts between nurses. The binary goal programming model that has been developed can aid head nurses in scheduling by offering a template of schedules where hospital policies are satisfied and nurses? preferences are considered.